Propossal for the optimization design and operation of autonomus photovoltaic systems installed in Peru based on smartgrids - Morales Taquiri, Oswaldo Morla (2015)
Climate change forces economic growth without pollution. One of the main alternatives is the use of renewable energy such as solar photovoltaic. The variability of the solar resource, the demand and the environmental conditions that will affect its performance. For the proper functioning of autonomous photovoltaic systems, it is indispensable to develop a methodology for optimizing its design and operation, autonomous, taking into account the supply, demand and environmental conditions, using criteria for intelligent electric grids. This project proposes the monitoring and prediction of the performance of photovoltaic systems, as well as the promotion of efficient planning and control strategies. It is proposed to use a maximum power point tracking controller, a weather station that includes dust measurement, a wireless data acquisition system, and a LabVIEW based monitoring and registration station.